2017
DOI: 10.14744/nci.2017.98705
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the vitamin b12 deficiency with peripheral neuropathy in the type 2 diabetes mellitus using metformin

Abstract: OBJECTIVE:The relationship between vitamin B12 deficiency and peripheral neuropathy has been shown in a number of previous studies. Metformin is the indispensable first-line treatment for type 2 diabetes mellitus (DM) worldwide. One of the adverse effects of the use of metformin is vitamin B12 deficiency. In the present study, we investigated the relationship between vitamin B12 deficiency and peripheral neuropathy due to the use of metformin.METHODS:Patient’s laboratory and electromyography (EMG) data were re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 11 publications
2
10
1
1
Order By: Relevance
“…Similar findings have been previously reported in different settings. 20,[47][48][49] In the current study, NTSS-6 was used to assess neuropathy. The tool is prone to subjectivity as it is symptom dependent, and there is a possibility of misclassification of participants.…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings have been previously reported in different settings. 20,[47][48][49] In the current study, NTSS-6 was used to assess neuropathy. The tool is prone to subjectivity as it is symptom dependent, and there is a possibility of misclassification of participants.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are conflicting reports on the association between Metformin-induced B 12 deficiency and neuropathy, with some reports showing an association ( 14 , 15 ) while others have refuted this ( 11 , 16 18 ). Furthermore, in a recent study from Turkey, while the prevalence of B 12 deficiency was 38.4% there was no difference in B 12 levels in those with and without neuropathy ( 19 ). Despite this there is wide spread administration of vitamin B 12 therapy in patients in the Middle East and Far East, with a recent analysis from five teaching hospitals in Jordan, indicating that cyanocobalamin (B 12 ), was the second most common injectable therapy after insulin ( 20 ).…”
Section: Introductionmentioning
confidence: 91%
“…4 It has also been reported that vitamin B 12 deficiency ranges from 9% to 52% in people with T2DM and has been partially attributed to long-term use of metformin. [5][6][7] Vitamin B 12 is essential for remethylation of homocysteine (Hcy) to methionine and B 12 deficiency could lead to hyperhomocysteinemia, which has been associated with macrovascular complications in people with T2DM. 8 B 12 deficiency may also increase the severity of peripheral neuropathy in T2DM.…”
Section: Introductionmentioning
confidence: 99%